Plasma Thromboplastin Component (Christmas Factor, Factor IX) Levels in Stored Human Blood and Plasma - Dieter Geratz, J; Graham, John B. (Thrombosis and Haemostasis, 1960)
1. PTC activity was assayed in 26 units of human plasma prepared from whole blood stored for 3 weeks at 4° C. The plasma had been frozen and stored at — 20° C for additional periods ranging from a few days to 4 months. High PTC activity was still present in the plasma at the end of this period, the activity averaging 95% of normal.2. The PTC activity of 19 samples of “reclaimed“ plasma stored for an additional 6 months at — 20° C decreased by an average of 23%. This decrease was statistically significant.3. Liquid plasma kept at room temperature for 5½—7½ months contained no PTC activity.4. Lyophilized plasma stored at room temperature for 6—8 years contained an average of 30% PTC activity. Lyophilized plasma stored at — 20° C for 4 years contained 68% PTC activity.5. ACD and disodium hydrogen citrate anticoagulant solutions served equally well in preserving PTC activity in whole blood stored in glass tubes over a period of 3 weeks at 4° C.6. “Reclaimed“ plasma from outdated bank blood provided effective hemostasis in two operations for the removal of 20 teeth from a severely PTC-deficient patient.7. The high PTC activity of “reclaimed“ plasma was confirmed by the close agreement between the PTC level expected in a PTC deficient patient after transfusion of such plasma and that observed.